Grain refinement of C-Mn steel through thermo-mechanical processing. Issue 2 (5th May 2015) - Rethinam, Archana; Shivakumar, Vinoo D.; Harish, L.; Abhishek, M.B.; Ramana, G.V.; R., Madhusudana; Sah, R.; Manjini, S.
Abstract : Purpose: – The application of new technologies requires, however, modern rolling mills. Indeed, in manufacturing plants of older types, strict compliance with the developed rolling regimes is not always feasible. Improving the mechanical properties in such cases is possible only by means of cooling. Compressive deformation behavior of carbon–manganese (C-Mn) grade has been investigated at temperatures ranging from 800-900°C and strain rate from 0.01-50 s−1 on Gleeble-3800, a thermo-mechanical simulator. Simulation studies have been conducted mainly to observe the microstructural changes for various strain rate and deformation temperatures at a constant strain of 0.5 and a cooling rate of 20°C s−1. Design/methodology/approach: – The project begins with simulation of a hot rolling condition using the thermo-mechanical simulator; this was followed by microstructural examination and identification of phases present by using an optical microscope for hot-rolled coil and simulated samples; grain size measurement and size distribution studies; and optimization of finishing temperature, coiling temperature and cooling rate by mimicking plant processing parameters to improve the mechanical properties. Findings: – As the strain rate and temperature increase, pearlite banding decreases gradually and finally gets completely eliminated, thereby improving the mechanical properties. True stress–strain curves were plotted to extrapolate the effect of strain-hardening and strain rate sensitivity on austenite (γ) and austenite–ferrite (γ-a) regions. To validate the effect of strain rate and temperature over the grain size, the hardness of simulated samples was measured using the universal hardness tester and the corresponding tensile strength was found from the standard hardness chart. Practical implications: – The results of the study carried out have projected a new technology of thermo-mechanical simulation for the studied C-Mn grade. These results were used to optimize the plant processing parameter like finishing and coiling temperature and finishing stands strain rate. Originality/value: – By controlling the hot rolling conditions like finishing, coiling temperature and cooling rate, structures differing in mechanical properties can be obtained for the same material. Accurate understanding of a structure being formed when different temperatures are applied enables the control of the process that assures intended structures and mechanical properties are achieved.